Association Between Three Different Cognitive Behavioral Alcohol Treatment Programs and Recidivism Rates Among Male Offenders: Findings from the United Kingdom. (2nd May 2015) - Needham, Marie; Gummerum, Michaela; Mandeville‐Norden, Rebecca; Rakestrow‐Dickens, Janine; Mewse, Avril; Barnes, Andrew; Hanoch, Yaniv
<x xml:space="preserve">Abstract</x> Background Cognitive behavioral therapy‐based alcohol treatment programs have been widely used to break the link between alcohol and crime. While evidence exists on the connection between alcohol and crime, there is little data that demonstrate the effectiveness of different alcohol treatment programs in reducing criminal behavior. We tested whether male offenders who participate in alcohol treatment programs show lower rates of recidivism than a matched offender group who did not participate in an alcohol prevention program. Methods This is an observational matched case–control study. Participants were 564 male offenders with an alcohol problem related to offending. Participants were assigned by the courts to 1 of 3 alcohol treatment programs (141 offenders per treatment): Low Intensity Alcohol Program (LIAP), Alcohol Specified Activity Requirement, and Addressing Substance‐Related Offending. A fourth matched group (n = 141) was not assigned to a program and served as a control group. Survival analysis was used to calculate participants' charged and reconviction rates over 4 time periods (0 to 3, 4 to 6, 7 to 9, and 10 to 12 months after completion of program or order). Results Offenders who did not participate in a program were more than twice as likely to be charged compared to offenders who participated in a program. Furthermore, offenders who did not participate in a program were over 2.5 times more likely to be reconvicted. Among the 3 alcohol treatment programs evaluated, the LIAP was the most cost‐effective. Conclusions Offenders enrolled in an alcohol treatment program showed a significant reduction in being charged with or reconvicted of a crime. With costs of keeping offenders in prison per year reaching close to £40, 000 per offender per year (Mulheirn et al., 2010, www.smf.co.uk), assigning offenders to alcohol preventive programs—such as LIAP—are a promising way to reduce recidivism and reduce cost.